Allelopathic effects of the aqueous extract of Rhazya stricta on growth and metabolism of Salsola villosa. (2nd November 2018) - Alqarawi, Abdulaziz A.; Hashem, Abeer; Kumar, Ashwani; Al-Arjani, Al-Bandari Fahad; Abd_Allah, Elsayed Fathi; Dar, Basharat A.; Wirth, Stephan; Davranov, Kakhramon; Egamberdieva, Dilfuza
Abstract: Allelopathy is a biological process in which plants synthesize allelochemicals that affect the physiological properties, development and survival of other plants. Experiments were conducted to investigate the allelopathic effect of Rhazya stricta leaf extracts on the germination, early seedling growth and metabolism of Salsola villosa . Aqueous extracts (10, 30 and 50 g/ L) decreased germination and growth by reducing the synthesis of chlorophyll pigments. Leachate treatments induced the antioxidant system by upregulating antioxidant enzyme activities. Additionally, the activities of phenylalanine ammonia lyase and indole acetic acid oxidase were stimulated by exposure to leachate. R . stricta leachates reduced the content of polyunsaturated membrane fatty acids with a concomitant increase in the saturated ones. Unsaturated fatty acids were reduced with the increased concentration of leachate. Phospholipids were also reduced due to leachate, thereby affecting membrane functioning considerably. Aqueous extracts from the leaves of R . stricta restrict the growth and metabolism of S . villosa by hampering membrane functioning and photosynthetic capacity.